Ikimokyklinio ugdymo pedagogų požiūris į įtrauktį ir įtraukųjį ugdymą - Čarnická , Marcela; Kušnírová , Veronika; Rochovská, Ivana; Šilonová, Viera (Special Education, 2023)
The research focuses on the attitudes of kindergarten teaching staff (teachers and pedagogical assistants) towards inclusion, their views on the problems they encounter in the education of children with special educational needs and their views on the importance of the measures introduced in the education of these children. Two questionnaires were used for data collection. Attitudes through a questionnaire by the researcher Marian Mahat (MATPIES) were measured. The second questionnaire of own construction consisted of six questions, two of which focused on the problems encountered by educators in the education of children with special educational needs and their views on the importance of the measures introduced for these children. The questionnaire was completed by 284 kindergarten teaching staff members. The correlation between the degree of problems reported by teaching staff in the education of children with special needs and the attitudes of teaching staff towards inclusion was not confirmed. The correlation between the assessment of the need for measures for successful inclusive education and the attitudes of teaching staff towards inclusion was not statistically significant.